A Comparative Analysis of Firm Risk Influence on Working Capital Investment Decisions in Developed and Emerging Economies - Pitt, Lucian J (Universitas Nahdlatul Ulama Surabaya, 2024)
This study delves into the correlation between a company's decision to invest in working capital and a diverse range of internal (firm-specific) and external risks. Employing dynamic panel data estimation, it analysed data from 2,996 firms in developed and emerging economies. The findings robustly support the anticipated relationship between a company's risks and its investment in working capital, except market risks. Furthermore, the study uncovers that this correlation is more pronounced for firms in developed economies than those in emerging economies, potentially attributable to more accessible access to working capital funding and more formal planning processes. These results significantly contribute to filling a gap in academic research in corporate finance relating to the influence of firm risk on working capital investment decisions in developed and emerging economies.